Development of a Prognostic Model for Ovarian Cancer Patients Based on Novel Immune Microenvironment Related Genes - Wang, Wei; Wu, Qianqian; Wang, Ziheng; Ren, Shiqi; Shen, Hanyu; Shi, Wenyu; Xu, Yunzhao (Frontiers in Oncology, 2021)
Ovarian cancer (OV) has become the most lethal gynecological cancer. However, its treatment methods and staging system are far from ideal. In present study, taking the advantage of large-scale public cohorts, we extracted a list of immune-related prognostic genes which differentially expressed in tumor and normal ovarian tissues. Importantly, an individualized immune-related gene based prognostic model (IPM) for OV patients was developed. Furthermore, we validated our IPM in Gene Expression Omnibus (GEO) repository and compared the immune landscape and pathways between high-risk and low-risk groups. The results of our study can serve as an important model to identify the immune subset of patients and has potential for use in immune therapeutic selection and patient management.